Stewards of Memory : The Past, Present, and Future of Historic Preservation at George Washington's Mount Vernon - Reinhart, Thomas A.; Pecoraro, Luke J.; Cadou, Carol Borchert (Book collections on Project MUSE., 2018)
"This book focuses on historic preservation issues at George Washington's Mount Vernon"--